Anthropology’s Ancestors: A review essay of a new Berghahn collection - Pina-Cabral, Joao (2022)
Anthropological history is today a growth area. This essay reviews the new collection Anthropology’s Ancestors that Aleksandar Boskovic is editing at Berghahn. The three short books he has published so far are very engaging intellectual histories of three anthropologists of the past who have recently received increased critical attention and whose legacy certainly deserves it: Robertson Smith, Margaret Mead and Françoise Héritier.